Disseminated adenovirus infection in a patient with relapsed refractory multiple myeloma undergoing autologous stem cell transplantation and pomalidomide/dexamethasone as salvage regimens. Issue 5 (May 2019) - Yasuda, Shunichiro; Najima, Yuho; Konishi, Tatsuya; Yamada, Yuta; Takezaki, Toshiaki; Kurosawa, Shuhei; Sakaguchi, Masahiro; Harada, Kaito; Yoshioka, Kosuke; Igarashi, Aiko; Inamoto, Kyoko; Toya, Takashi; et al.
Abstract: Background: Disseminated adenovirus (ADV) infection is a fatal complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT), however, it is rare following autologous peripheral blood stem cell transplantation (auto-PBSCT) or chemotherapy alone. Case: A 66-year-old Japanese female with relapsed and refractory multiple myeloma (RRMM) received auto-PBSCT, achieving partial response. To obtain a greater response, pomalidomide/dexamethasone was started on day 28 after auto-PBSCT, but was stopped on day 41 due to thrombocytopenia, fever, and gross hematuria. Additionally, she complained of abdominal pain on day 46. Blood tests revealed elevation of transaminases and alkaline phosphatase. There was no evidence of bacterial or fungal infections or progression of MM. ADV titer in urine and serum were 3.41 × 10 5 copies/mL and 6.76 × 10 3 copies/mL, respectively. CT scans revealed cystitis, urethritis, and peritonitis. Since more than two organs were infected with ADV, she was diagnosed with disseminated ADV disease. After 5 weeks of supportive care, all symptoms resolved. ADV titer decreased to 5.90 × 10 2 copies/mL in urine and became negative in serum on day 80. However, she succumbed to the MM a little more than a month later. Conclusion: Disseminated ADV infection can occur even in non-allogeneic transplant settings, such as in severely immunocompromised patients with MM who receive auto-PBSCT and repeated salvage therapies. Although it is a rare event, the mortality rate of this disease is very high, and hence, early diagnosis and interventions are needed in suspected cases.